Online communication and assessment practices during the Covid Pandemic: a study of the portuguese higher education students’ perceptions - Morgado, Lina (2022)
Financed national funds through FCT – Fundação para a Ciência e a Tecnologia, I.P., under the projects UIDB/04372/2020